IOT Based Accident Detection and Vehicle Tracking System Using GPS and GSM Module - Ahay Khattar, Pratim Sarkar, J.Selvin Paul Peter (International Journal of Advanced Science and Technology, 2020)
With the increase in technology and motor    vehicle production the number of road accident has increased. The survival rate after accident is very low as proper emergency facilities are not available. Our project would help in detecting an accident and determine its location and the location is dispatched to rescue team and emergency contacts of the rider. The existing models are not reliable as they use vehicle distance between two vehicle provided by certain sensors and does not show concern about speed. Very slow emergency facility can also be a drawback that can be solved by our model. Keywords: IOT, Accident detection, GSM, GPS sensor.